2014
DOI: 10.4161/epi.27906
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain proteins are required for glioblastoma cell proliferation

Abstract: Epigenetic proteins have recently emerged as novel anticancer targets. Among these, bromodomain and extra terminal domain (BET) proteins recognize lysine-acetylated histones, thereby regulating gene expression. Newly described small molecules that inhibit BET proteins BRD2, BRD3, and BRD4 reduce proliferation of NUT (nuclear protein in testis)-midline carcinoma, multiple myeloma, and leukemia cells in vitro and in vivo. These findings prompted us to determine whether BET proteins may be therapeutic targets in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 30 publications
8
124
0
Order By: Relevance
“…We previously demonstrated that the BET bromodomain inhibitor I-BET151 reduces cell proliferation in both GBM cell lines and patient-derived cells in vitro and in vivo (4). Therefore, we asked whether I-BET151 treatment reduced HOTAIR expression in GBM cells and found that treatment of LN18 cells with I-BET151 for 24 h reduces the expression of HOTAIR by ∼80% (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the BET bromodomain inhibitor I-BET151 reduces cell proliferation in both GBM cell lines and patient-derived cells in vitro and in vivo (4). Therefore, we asked whether I-BET151 treatment reduced HOTAIR expression in GBM cells and found that treatment of LN18 cells with I-BET151 for 24 h reduces the expression of HOTAIR by ∼80% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HOTAIR is a transcript necessary for glioblastoma proliferation, and it appears to be the most relevant lncRNA target of this drug. Our findings invoke a previously unidentified important mechanism of action of BET bromodomain inhibitors, which would in part explain the efficacy of this drug in blocking the proliferation of GBM cells in vivo and in vitro (4,15).…”
Section: Significancementioning
confidence: 89%
“…126 A number of preclinical studies has been performed in GBM models with the BRD inhibitors JQ1 and I-BET151, showing promising antitumor activity. 135,136 Moreover, OTX015 (MK-8628), a novel BET inhibitor, has been tested recently at the clinical level in dose-finding studies in GBM patients (NCT02296476), and displays in vitro and in vivo antitumor effects alone and in combination with conventional therapies in GBM models. 126 The safety and tolerability of another BET inhibitor, INCB057643, is also currently being tested in subjects with GBM (NCT02711137) ( Table 2).…”
Section: Bromodomain and Extraterminalmentioning
confidence: 99%
“…BET I-BET151 I-BET151 specifically targets the recognition of acetylated lysine residues of BETs (131) Inhibits GBM cell proliferation (135) wild type for H3, a fifth pediatric glioblastoma line that carries the H3.3 G34V mutation, and isogenic cell lines derived from human astrocytes with and without transgene expression of the H3.3 K27M mutation. 108 Both patient-derived cell lines had global hypomethylation of H3K27 compared with the wild type models.…”
Section: H3k9mtsmentioning
confidence: 99%
“…In addition to recruitment and functioning around on gene promoters, Brd4 is also recruited to subsets of distal enhancers to promote gene transcription [14] . Various BET small molecule inhibitors successfully block BET protein recruitment and BET-mediated transcriptional activity [15][16][17] , and the function of these inhibitors has been explored in various disease settings including cancer [4,[18][19][20][21] , autoimmune response [4] , osteoporosis [22,23] and atherosclerosis [24] . Here we will focus our discussion on how BET inhibition affects inflammatory responses.…”
Section: Chromatin Regulation and Bet Proteins In Transcriptional Actmentioning
confidence: 99%